Strong perpendicular anisotropic ferromagnet Fe3GeTe2/graphene van der Waals heterostructure. (2nd March 2023) - Zhao, Bing; Karpiak, Bogdan; Hoque, Anamul Md; Dhagat, Pallavi; Dash, Saroj P
Abstract: Two-dimensional magnets offer a new platform for exploring fundamental properties in van der Waals (vdW) heterostructures and their device applications. Here, we investigated heterostructure devices of itinerant metallic vdW ferromagnet Fe3 GeTe2 (FGT) with monolayer chemical vapor deposited graphene. The anomalous Hall effect measurements of FGT Hall-bar devices exhibit robust ferromagnetism with strong perpendicular anisotropy at low temperatures. The electrical transport properties measured in FGT/graphene heterostructure devices exhibit a tunneling transport with weak temperature dependence. We assessed the suitability of such FGT/graphene heterostructures for spin injection and detection and investigated the presence of FGT on possible spin absorption and spin relaxation in the graphene channel. These findings will be useful for engineering spintronic devices based on vdW heterostructures.